COVID-19 and monkeypox co-infection: A rapid systematic review - El-Qushayri, Amr Ehab; Reda, Abdullah; Shah, Jaffer (Frontiers in Immunology, 2022)
COVID-19 still constitutes a remarkable burden on countries and their healthcare systems even with the remarkable advances in the vaccine industry. COVID-19 patients are liable to various complications, and those with co-morbidities and associated infections are usually the most vulnerable (1, 2). Recently, a multi-country outbreak of monkeypox virus (MPV) occurred and the World Health Organization declared it a Public Health Emergency of International Concern. Accordingly, certain concerns aroused regarding the outcomes of patients co-infected with COVID-19 and MPV. To collect all the papers that reported COVID-19 and MPV co-infection, we searched in five databases: PubMed (131), Virtual Health Library (122), Google Scholar (75), Web of Science (79), and Scopus (108). On 2nd October, we used the search term “("monkeypox virus" OR "MPV" OR "monkey pox" OR "monkeypox") AND ("COVID-19" OR "COVID 19" OR "novel coronavirus" OR "SARS‑CoV‑2")” through all the databases and adapted it to fit the search process in each database. The literature search resulted in 3 articles reporting 3 cases of COVID-19 and MPXV co-infection (Table 1). All cases were male patients, who had sex with men prior to the infection, had multiple comorbid conditions, were diagnosed with PCR, and were admitted to the hospital. The length of hospital stay was 4, 6, and 9 days. On admission, two cases had multiple vesicular lesions on various sites of the body associated with tonsillar inflammation, while the third case had genital ulcers and inguinal lymph node enlargement. All cases were managed in the hospital and recovered well.